Baroreflex sensitivity and cardiovascular mortality in patients with mild to moderate heart failure. Issue 6 (June 1995) - Osterziel, K. J.; Hänlein, D.; Willenbrock, R.; Eichhorn, C.; Luft, F.; Dietz, R.
Abstract : OBJECTIVE--To assess the influence of both sympathetic (plasma noradrenaline concentrations) and parasympathetic (baroreflex activation) tone on survival in patients with congestive heart failure. DESIGN--Invasive study with determination of parasympathetic activity and follow up for at least 4.5 years. SUBJECTS--35 patients with sinus rhythm and mild to moderate heart failure (New York Heart Association grades II-III) (mean age 53 (SD 3)). RESULTS--20 patients whose hearts survived were compared with 15 patients whose hearts did not (12 died and three received transplants). The two groups differed significantly in terms of mean arterial blood pressure (98 (3) v 90 (3) mm Hg), heart rate (82 (2) v 93 (4) beats/min), and mean pulmonary artery pressure (24 (3) v 35 (2) mm Hg) (all P < 0.05), while cardiac index, stroke volume index, and right atrial pressures were not different. The survivors had significantly lower plasma renin activities (3.6 (0.8) v 9.0 (3.6) angiotensin I/ml/h; P < 0.05) and tended to have lower noradrenaline values than non-survivors (170 (23) v 286 (74) pg/ml) at baseline. Baroreflex sensitivity was significantly lower in non- survivors than in survivors (1.3 (0.2) v 2.3 (0.3) ms/mm/Hg); P < 0.02). As the time of cardiac transplantation is dependent on complex logistical factors the three patients who received a transplant were excluded from the analysis of survival time. The risk of death in relation to baroreflex sensitivity at the median sensitivity of 1.48 ms/mm Hg was calculated. Survival was significantly different (P < 0.04) between the resulting two groups; three of the 16 subjects with high baroreflex sensitivity died compared with nine of the 16 with a baroreflex sensitivity < 1.48 ms/mm Hg. When systemic blood pressure, pulmonary artery pressure, stroke volume index, plasma noradrenaline concentrations, and baroreflex sensitivity were entered into a Cox proportional hazards regression, only systolic blood pressure and plasma noradrenaline values predicted survival (P < 0.001). CONCLUSIONS--Low vagal tone is correlated with a poor prognosis in patients with heart failure. Sympathetic tone measured as plasma noradrenaline concentration also contributed to survival. An additional contribution of vagal tone to survival could not be shown when sympathetic tone was considered simultaneously. This may be due to the inverse relation of sympathetic and parasympathetic tone and to the insensitivity of the multiple regression method to identify additional risk factors in small numbers of patients.